Production Management of Chemical Industries - Golwalkar, Kiran R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers all major areas of operation, pollution control, safety, modernization, diversification, and resource management for cost control in the industrial production of chemicals. The author details the importance of obtaining the right type of raw materials and equipment for maximum plant efficiency and also discusses revival of plants that have been idle for long periods. He also presents important issues concerning product quality, energy recovery, safety, pollution control and improving profitability by proper management of resources. The book is ideal for shop floor engineers, middle level management, and owners of small- and medium-scale facilities in many countries as it serves as a guide for keeping the plant operations running in adverse situations, for reducing energy consumption; improving profitability, resource allocation, and workforce planning.
Introduction -- Financial and Commercial Matters -- Procurement of Equipment and Machinery -- Erection and Commissioning -- Procurement of Raw Materials and Other Items -- Safety Management -- Pollution Control -- Maintenance Management Activities -- Utilities -- Instrumentation -- Energy Efficiency -- Methods of Heating -- Inventory Control -- General Administrative Matters -- Process Control, Product Quality, Research & Development -- Smooth Running of the Production Plants -- Identification of Hazards: Some Practical Examples -- Appendix A: General Technical Matters -- Appendix B: Techno-economic Matters -- Appendix C: Typical Water Balance in Chemical Industries -- Appendix D: Typical Electrical Arrangements -- Appendix E: Organisation Structure for Industrial Administration.
Keywords: Chemistry, Technical; Industrial Management; Production management; Industrial Chemistry; Industrial Management; Operations Management